MENAKAR KETEGUHAN INTEGRITAS PENGADIL DI TENGAH PUSARAN SUAP DAN INTERVENSI KEKUASAAN - Kontesa, Agnesia Fifin; Klau, Anastasia Suputri; Banase, Yohanes P; Lao, Maria Jesnita Melania; Ratnasari, Auliya; Lewokeda, Angelia Hunu Ola; Sonbai, Victor; Mas'ud, Fadil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A judge’s integrity is a crucial aspect in upholding the rule of law and public trust in the judicial system. This study aims to evaluate the resilience of judicial integrity in the face of bribery and interference by those in power, while also assessing the effectiveness of the implementation of the code of ethics by the Judicial Ethics Council (MKH). The method applied in this study is a normative legal approach with data analysis from scientific articles, books, and laws. The findings indicate that judicial integrity depends not only on individual moral values but also on institutional responsibility in upholding justice and the validity of the law. Bribery and intervention by those in power are the primary factors undermining judicial independence, while the MKH’s enforcement of the code of ethics has not yet fully succeeded in serving as a deterrent. This study concludes that to strengthen judicial integrity, a systemic approach is needed through reforms in oversight, the enforcement of the code of ethics, and the promotion of moral values within the legal profession.